Engineering Vibration Recognition Using CWT-VGG19 - Wei Huang; Jian Xu (Shock and Vibration)
Multisource signal recognition is a common problem in engineering vibration control. Given that traditional methods often primarily rely on prior knowledge and expertise, which can limit efficiency and accuracy, this study proposed a vibration recognition model based on VGG19, utilizing continuous wavelet transform to combine signal processing with deep learning techniques. The continuous wavelet transform converts the original one-dimensional vibration signals into two-dimensional time-frequency representations with richer feature information, which are then input into the convolutional layers for automatic feature extraction, culminating in vibration recognition through the SoftMax layer. To evaluate the model’s performance, 20 sets of measured vibration data were tested. The results show that the proposed model achieves a recognition accuracy of 99%, excelling in both component recognition and the separation of vibration signals. Therefore, this study is of great significance for engineering vibration diagnosis, the front-end design of vibration control, and the analysis and optimization of control effectiveness.